Implementasi Surat Edaran Otoritas Jasa Keuangan Nomor 6 Tahun 2017 tentang Penetapan Tarif Premi Asuransi Umum pada PT. Asuransi Jasa Indonesia Syariah Medan - Fitri, Khairizal; Hartono, Budi; Isnaini, Isnaini (Mahesa Research Center, 2022)
The purpose of this paper is to find out the implementation of SE OJK number 6 of 2017 concerning the Determination of General Insurance Premium Rates, which has been implemented and carried out by PT. Jasindo Syariah Medan. This research method uses a descriptive qualitative approach. Through observation research instruments, interviews and documentation studies. The data analysis using descriptive analysis. The results of the research are expected to show that the implementation of SE OJK number 6 of 2017 concerning the Determination of General Insurance Premium Rates at PT. Insurance Services Indonesia Syariah Medan. The researcher concludes that the implementation in terms of communication has been going well for several parties, especially the OJK and the public as insurance consumers. However, in terms of human resources (HR), the implementation is considered still not optimal, because there are still insurance agents who do not understand the contents of SE OJK number 6 of 2017. In terms of disposition, PT Asuransi Jasa Indonesia Syariah Medan is very supportive. good with OJK rules, while in terms of bureaucratic structure it has been running well according to OJK standards.